Providing a Human Resource Management Model based on Knowledge Management in Sari Executive Organizations - Shah Moradi, Mahsa (2020)
Executive organizations need to design strategic processes in order to use effective human resources for increased productivity. So, this research aimed to provide a human resource management model based on knowledge management in executive organizations in Sari, Iran. This research is applied in terms of purpose and its method is survey research. The nature of this study is descriptive with the type of correlation. The statistical population includes: 1) 15 experts familiar with the field of human resource management who were selected using the selective method; 2) employees who work in the executive organizations of Sari (29,697 people) who, according to the Cochran formula, selected 400 people by random sampling by conglomerate method. Data collection was performed using a human resources management research questionnaire with 54 questions and knowledge management with 24 questions. The CVR was calculated as 0.97.4 and 0.95.1, respectively, and was acceptable. Cronbach's alpha coefficient was also estimated above 0.7, confirming the reliability of the instrument. In the data analysis, route tests and structural equation models were used using the Lisrel software. Based on the result, the strength of the relationship between the variables of human resource management and knowledge management was calculated at 0.48, which showed that the correlation is strong and desirable. The t statistic (4.99) was also greater than the critical value of t at the 5% error level, that is, 1.96, indicating that the correlation was significant. In conclusion, it can be said that human resource management and knowledge management as two coordinating components play a determining role in the organization's competitiveness with each other, and organizations that pay attention to these important components will definitely achieve their development and excellence. desired.